INCREASING USE OF FOOD PRESERVATIVES IN MODERN TIMES (International Journal of Food and Nutritional Sciences, 2022)
Safe food has been the mantra of safe life since ancient times. Food, clothing, shelter are the basic needs of human beings. Food is an essential element for the functioning of the human body. Since food is available to us from the elements of nature, humans do not feel the need to make a separate effort for it. In today's era of increasing pollution, food is essential for the body in order to keep our standard of living safer. As humans will always need food and the current food wastage, there is concern about the future of food preservation. For that it is important to understand how to preserve food. Because while preserving food, it is necessary to pay attention to how the quality of food will be increased without reducing it in any way in terms of health. For food preservation, food preservatives in various forms such as domestic, chemical, antibiotic are used to preserve meat, mutton, fish, sea food and other foods. Therefore, in today's time, it is necessary to recognize the need for food protection and think about it.